2014
DOI: 10.1016/j.elecom.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry in supercritical fluids: A mini review

Abstract: A brief overview of the literature relating to electrochemical studies and processes undertaken in supercritical fluids is presented. This review mostly concerns carbon dioxide and hydrofluorocarbons, given the accessibility of their supercritical states, and does not consider the emerging body of research in expanded phase electrochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…These include the development of structurally complex gas-diffusion electrodes for use in flow cells, [26,27] polymer electrolytes, [28,29] and ionicl iquids [30] that leverage tailorede lectrode-contacting phases to favor high CO 2 availability.I ns ome cases, these approaches rely on interfacial phenomena [31] or involve preparation of membraneelectrode assemblies. [34][35][36][37] Furthermore, the high operating pressures neededt oa chieve supercritical conditions (> 7.38 MPa) pose practical challenges and increase costs. [32,33] However, scCO 2 is ap oor conductor and, even upon pairing with co-solvents, the solubility of most supporting electrolytes MultimolarC O 2 concentrations are achieved in acetonitrile solutions containing supporting electrolyte at relatively mild CO 2 pressures (< 5MPa) and ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the development of structurally complex gas-diffusion electrodes for use in flow cells, [26,27] polymer electrolytes, [28,29] and ionicl iquids [30] that leverage tailorede lectrode-contacting phases to favor high CO 2 availability.I ns ome cases, these approaches rely on interfacial phenomena [31] or involve preparation of membraneelectrode assemblies. [34][35][36][37] Furthermore, the high operating pressures neededt oa chieve supercritical conditions (> 7.38 MPa) pose practical challenges and increase costs. [32,33] However, scCO 2 is ap oor conductor and, even upon pairing with co-solvents, the solubility of most supporting electrolytes MultimolarC O 2 concentrations are achieved in acetonitrile solutions containing supporting electrolyte at relatively mild CO 2 pressures (< 5MPa) and ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…is too low ( 35 mm)tofacilitate high current densitiesand faradaic efficiencies. [34][35][36][37] Furthermore, the high operating pressures neededt oa chieve supercritical conditions (> 7.38 MPa) pose practical challenges and increase costs. Development of new reaction media could help in overcoming these challenges by enabling (1) higher CO 2 concentrations at more modest pressures, (2) sufficient conductivityt oe ngender rapid electron transfer,a nd (3) higherm ass-transfer rates of CO 2 to the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen from Figure Figures 7a and b we can obtain a value for the diffusion coefficient of DMFc using equation (1). These values are given in Table 2.…”
Section: Determination Of the Diffusion Coefficient Of Decamethylferrmentioning
confidence: 97%
“…However because of the difficulties of working at elevated pressures they have not been that widely studied or used in electrochemistry [1,2]. Recent studies have shown that supercritical fluids are of interest for electrodeposition [3][4][5][6][7], electrosynthesis [8][9][10], and as media for the electrochemical reduction of carbon dioxide [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that the membrane reactor combines catalytic reactions with separation properties of zeolite membranes. Supercritical fluid (SCF) is obtained when a compound surpasses its critical temperature (T C ) and pressure (P C ) [16]. At this point the fluid displays intermediate properties between a gas and a liquid, producing a unique medium with many of the advantages of both states of matter [17][18][19].…”
Section: Introductionmentioning
confidence: 99%